The Force of Love and the Institution of Marriage: A Study of The Guide, Candida, and Hayavadana - JITENDRA KUMAR MISHRA (International Journal of Language and Literary Studies, 2025)
The exploration of love and the institution of marriage has been a recurring theme in literature across cultures and epochs. It has been depicted as both a sanctified social contract and a restriction on personal freedom. The interplay between love and marriage, especially the ways in which love both disrupts and reaffirms the boundaries of marriage, has become a key concern for many authors. The works of R. K. Narayan, George Bernard Shaw, and Girish Karnad—The Guide (1958), Candida (1894), and Hayavadana (1971), respectively—offer profound insights into these themes. Through an exploration of these texts, we can see how love functions as a transformative, often rebellious, force against the confines of marriage. In this paper, we shall explore how each work presents love as a force that either challenges or subverts the institution of marriage. These three texts—while distinct in cultural, social, and historical context—share common themes in their exploration of love’s potential to disrupt, redefine, and revolt against the norms of marital relationships. Furthermore, by examining the characters’ relationships to love and marriage, we can understand the deeper philosophical questions these authors engage with, particularly concerning individual freedom, societal expectations, and human identity.